2017
DOI: 10.1002/jcla.22148
|View full text |Cite
|
Sign up to set email alerts
|

Association of ADIPOQ, leptin, LEPR, and resistin polymorphisms with obesity parameters in Hammam Sousse Sahloul Heart Study

Abstract: ADIPOQ, LEP, and RETN gene polymorphisms were associated with obesity parameters in HSHS population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 77 publications
1
21
0
1
Order By: Relevance
“…Previous studies also have been unable to detect the association between G2548A and obesity in Polish, Spanish, and Japanese population in which consistent with our data (Cieslak et al 2012;Mizuta et al 2008;Portolés et al 2006). However, the contradicting results were observed in Brazilian, Tunisian, Turkish, Taiwanese and French which G2548A variant was referred as one of the obesity markers (Boumaiza et al 2012;Hinuy et al 2008;Mammès et al 2000;Sahin et al 2013;Wang et al 2006;Zayani et al 2017). Besides, previous researchers suggested G allele was susceptible to the obesity in particular population (Boumaiza et al 2012) whereas, in some populations, they claimed that A allele was related to obesity risks (Hinuy et al 2008;Wang et al 2006).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies also have been unable to detect the association between G2548A and obesity in Polish, Spanish, and Japanese population in which consistent with our data (Cieslak et al 2012;Mizuta et al 2008;Portolés et al 2006). However, the contradicting results were observed in Brazilian, Tunisian, Turkish, Taiwanese and French which G2548A variant was referred as one of the obesity markers (Boumaiza et al 2012;Hinuy et al 2008;Mammès et al 2000;Sahin et al 2013;Wang et al 2006;Zayani et al 2017). Besides, previous researchers suggested G allele was susceptible to the obesity in particular population (Boumaiza et al 2012) whereas, in some populations, they claimed that A allele was related to obesity risks (Hinuy et al 2008;Wang et al 2006).…”
Section: Discussionsupporting
confidence: 82%
“…14 Polymorphisms in FTO, MC4R, ABCA1, and ADIPOQ were reported to be significantly associated with obesity and Type 2 diabetes mellitus (-T2DM). [15][16][17][18] Similarly, VDR variants, another set of moststudied SNPs, have been identified to be associated with many diseases, including obesity and increased adiposity. 19,20 GNPDA2, PFKP, and TCF7L2 showed a strong association with BMI, body weight, and waist circumference in genome association studies in Europe and Indian Asian.…”
Section: Introductionmentioning
confidence: 99%
“… 38 , 42 For example, a study that was conducted on overweight and obese children showed significantly higher leptin levels in rs7799039 AA genotype compared with other genotypes. 38 In addition, AA genotype was associated with higher risk of malnutrition inflammation syndrome, 24 obesity 25 and metabolic syndrome. 26 On the other hand, the CC genotype has been shown to be associated with dyslipidemia in patients using atypical antipsychotic agents.…”
Section: Discussionmentioning
confidence: 99%
“…Among LEP gene polymorphisms is rs7799039. The clinical significance of this polymorphism is well documented as it was associated with higher risk of several diseases including malnutrition inflammation syndrome, 24 obesity 25 and metabolic syndrome. 26 In addition, rs7799039 was associated with blood lipid levels among Southern Chilean population, 27 dyslipidemia in patients using atypical antipsychotic agents and lipid profile modulation induced by soluble fiber intake.…”
Section: Introductionmentioning
confidence: 99%